The role of transportation accessibility in regional economic resilience. (April 2020) - Chacon-Hurtado, Davis; Kumar, Indraneel; Gkritza, Konstantina; Fricker, Jon D.; Beaulieu, Lionel J.
Abstract: Whereas the importance of transportation for economic growth is widely acknowledged, past studies on the resilience of regions to economic shocks have not given explicit attention to the role of transportation accessibility on building robust regional economies. This exploratory study examines the regional performance in six U.S. states during the last recession (2008–2009) and post-recession (2010–2014) and evaluates its association with the transportation infrastructure. To account for spatial dependence and interactions, a exploratory spatial data analysis (ESDA), a global spatial autoregressive model, and a local Geographically Weighted Regression (GWR) are employed. Results show that, after controlling for other key aspects of resilience, such as industrial diversity and human capital, the global relationships between rail density, access to intermodal services, and access to local and regional markets were positively associated with regional performance (measured as competitive effect) during the recession. Similarly, positive regional performance before the recession period was associated with positive performance during the recession. The local spatial analysis, however, shows that the associations between the explanatory variables and regional performance vary significantly across space. The analysis and results of this study can contribute to a better understanding of the complex interactions between economic resilience and transportation infrastructure, and guide the development of policies and practices designed to strengthen the ability of regions to be resilient to economic shocks.